Design and operation of closed-loop triple-deck buck-boost converter with high gain soft switching - S. Narasimha; Surender Reddy Salkuti (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents the design and operation of three-stage buck-boost converter with high gain soft switching using closed loop proportional integral (PI) controller. The proposed converter is designed by arranging three identical buck-boost converters working in parallel. The converter units are connected to each other by an inductor as a bridge. This inductor plays a vital role in soft switching operation of converter by maintaining the voltage applied to switches at zero voltage at switching intervals, i.e., the zero-voltage switching (ZVS). The closed-loop system is designed by PI controller, and it maintains the output constant irrespective of changes in input, and the system becomes stable. The proposed converter is efficient in reducing switching losses, leading to improved converter efficiency. Due to parallel operation of three identical converters, the output voltage and input current contain fewer ripples than those of a single converter with same specifications. Proposed converter is more economical and reliable with simpler structure as it utilizes only two inductors as extra elements. The design and analysis of proposed circuit has been carried out in MATLAB Simulink by operating the circuit in various modes.